Women in Social Catholicism in Late Nineteenth- and Early Twentieth-century France - McMillan, James F. (Studies in church history, 1990)
This lecture should also have a sub-title, perhaps something like ‘a study in ambiguity’, because I want to use it as a particular example of the great paradox which seems to lie at the core of the relationship between women and the Church. On the one hand, as is well known, most varieties of Christianity have been marked by a more or less powerful misogynist strain which, understandably, has been the focus for feminist denunciations of the Church as one of the principal enemies of women’s rights. On the other hand, as ecclesiastical historians perhaps know better than others, Christianity cannot be viewed crudely as a force invariably responsible for women’s oppression, since from its beginnings it has proved itself specially attractive to women, allowing them to find inner peace and deep fulfilment through Church-related activities. I hope to show tliat the history of women’s involvement in the social Catholic movement in France in the period before the First World War is a perfect illustration of the paradoxical situation in which, within the framework of a potentially restrictive Christian discourse, women have been able to make a distinctive contribution both to their religion and to society in general.